Resettle…, beyond four walls. an analysis from the sustainable habitat, in the city of manizales, colombia (2010)
Faced to the vulnerability of urban populations exposed to natural hazards, the Colombian municipalities have the obligation to propose solutions, among others, through processes of resettlement by the acquisition of new or “used” housing purchased by the vulnerable community, in a safe site from a physical-natural point of view. The purpose of this paper is to analyze in a comparative way (habitat of destination/habitat of origin) the related projects in the Andean city of Manizales with a multidimensional vision, through the concepts of habitat, vulnerability, development and sustainability, relying on the implementation of about 600 surveys with the resettled people and interviews with those responsible for the local administration in charge of the resettlement programs. The aim of the study is to reach the construction of a method that, from indicators, optimizes the processes of resettlement or urban reform more generally.